The Relationship between Anxuety and Self-Confidence of Female Futsal Players ehen Facing a Match - Muhamad Aldi Fauzi; Sri Widaningsih; Henry Asmara (STKIP Pasundan Press, 2026)
This study aims to determine the extent of the relationship between anxiety and self-confidence among female futsal players when facing matches at SMP Negeri 1Kutawaringin. The background of this research is the phenomenon of many female futsalathletes experiencing anxiety during competitions, which affects their performance andself-confidence on the field. The results of this study are expected to provide an overview of the relationship between anxiety and athletes' self-confidence, as well as offer input for coaches, players, and related parties in efforts to improve performance and create a more conducive match atmosphere. Based on the research conducted on 30 female futsal athletes at SMP Negeri 1 Kutawaringin, the data showed that most athletes were at a moderate level of anxiety, totaling 15 athletes (50%). Meanwhile, athletes with a high level of anxiety numbered 8 (26.7%), and the remaining 7 athletes (23.3%) had a low level of anxiety. Regarding self-confidence, the results showed that 14 athletes (46.7%) had a moderate level of self-confidence, 10 athletes (33.3%) had a high level of self-confidence, and 6 athletes (20%) had a low level of self-confidence.